The role of noninvasive ventilation in the management of type II respiratory failure in patients with myotonic dystrophy. Issue 3 (26th July 2021) - Rautemaa, Vilma; Roberts, Mark E.; Bentley, Andrew; Felton, Timothy W.
Type 1 myotonic dystrophy (DM1) causes sleep disordered breathing and respiratory failure due to a combination of obstructive sleep apnoea, reduced central drive and respiratory muscle weakness. Noninvasive ventilation (NIV) is commonly used for treating respiratory failure in neuromuscular disease; however, there have been few studies assessing the role of NIV in DM1. The aim of this retrospective service evaluation was to investigate the impact of NIV adherence on hypercapnia and symptoms of hypoventilation in patients with DM1. Data on capillary carbon dioxide tension ( P CO2 ), lung function, adherence to NIV and symptoms of hypoventilation were obtained from the records of 40 patients with DM1. Mean capillary P CO2 significantly reduced from 6.81±1.17 kPa during supervised inpatient set-up to 5.93±0.82 kPa after NIV set-up (p<0.001). NIV adherence reduced from 7.8 (range: 1.0–11.0) h per 24 h during supervised inpatient set-up to 2.9 (0–10.4) h per 24 h in the community. Overall 72% of patients used NIV <5 h per 24 h during follow-up, including 11% who discontinued NIV completely. There was no correlation between adherence to NIV and changes in capillary P CO2 . Patients who reported symptomatic benefit (50%) had higher adherence than those who did not feel benefit (p<0.05). In conclusion, in patients with myotonic dystrophy with Type II respiratory failure maintaining adherence is challenging. Commencing patients with myotonic dystrophy on noninvasive ventilation appears to reverse respiratory failure despite poor adherence to ventilation https://bit.ly/343XUGK